2011
DOI: 10.1111/j.1439-0264.2011.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Collagen Fibres and Lysyl Oxidase Expression in the Presumptive Dermis of Chick Limb Bud

Abstract: Lysyl oxidase (LOX) plays a critical role in the formation of cross-linkages in extracellular matrix molecules. Thus, it is essential for the biogenesis and homeostasis of the connective tissue matrix. During development, collagen fibres and elastic system fibres emerge and accumulate in a temporospatial manner in the presumptive dermis of chicks. In this study, we investigated LOX mRNA expression by laser capture microdissection and RT-qPCR and LOX protein localization by immunohistochemistry. The picrosirius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Cell to fiber ratio at ED6 would be ∼2:1, when estimated by the present data (18.7 fibers in 50‐μm 2 area; Fig. 3A) and our previous data (23.3 cells in 40‐μm 2 area; Yamazaki et al, 2012). The possibility that a thicker fiber is formed by combining more than two thinner fibers together cannot be excluded completely and we indeed observed such cases in oxytalan fiber formation in the ED10‐chick gizzard (unpublished data).…”
Section: Discussionsupporting
confidence: 84%
“…Cell to fiber ratio at ED6 would be ∼2:1, when estimated by the present data (18.7 fibers in 50‐μm 2 area; Fig. 3A) and our previous data (23.3 cells in 40‐μm 2 area; Yamazaki et al, 2012). The possibility that a thicker fiber is formed by combining more than two thinner fibers together cannot be excluded completely and we indeed observed such cases in oxytalan fiber formation in the ED10‐chick gizzard (unpublished data).…”
Section: Discussionsupporting
confidence: 84%
“…We found large and rapid increases in total collagen content during tendon development (Fig. 3), while others have reported that LOX protein density is relatively constant during development in embryonic chick skin [34] and aorta [35]. Given this, perhaps the rate of collagen synthesis was outcompeting that of crosslink formation during HH 35 to 40, resulting in a decrease in the crosslink-to-collagen ratio.…”
Section: Discussionmentioning
confidence: 55%
“…LOX expression has also been shown to be closely correlated with elevated collagen I expression during development (36). However, no one has yet investigated the effects of collagen I crosslinking on metastatic tumor growth.…”
Section: Introductionmentioning
confidence: 99%